LARANGAN MUTLAK KEGIATAN PERTAMBANGAN DI WILAYAH PESISIR DAN PULAU-PULAU KECIL SEBAGAI BENTUK PERLINDUNGAN HAK ASASI NELAYAN DAN MASYARAKAT PESISIR - Nelina, Naswa; Oktavia, Mita; Ardini, Mira; Sansadila, Putri; Fatahillah, Ikhwan Aulia (Gapenas Publisher, 2024)
Mining activity is an economic activity that often has a negative impact on the environment. Mining activities in coastal areas have also generated protests and resistance from local communities. The coastal environment is one of the places where mining activities are often carried out. The majority of coastal communities work as fishermen. The beach environment has a big influence on their income. For coastal communities, mining activities not only take away their right to work but also take away their right to a decent living. Mining activities not only damage the environment but also take away the human rights of the surrounding communities. The government as the holder of power must provide protection for communities affected by mining activities. This protection is the Government's duty as stated in the preamble to the 1945 Constitution. This article provides further explanation regarding the urgency and formulation of the prohibition on this mining practice. This article uses a descriptive qualitative approach through library research as a form of research. The results and discussion are regarding the urgency of an absolute ban on mining activities in coastal areas and small islands in terms of human rights aspects and the formulation of a policy for an absolute ban on mining activities in coastal areas and small islands. The absolute prohibition on mining activities in coastal areas and small islands is based on two main urgencies, namely the vulnerability of environmental protection and the protection of the rights of coastal communities and small islands